Is There Gender (In)Equality in Pediatric Surgery? An Online Survey on Gender-Related Career Opportunities - Kueppers, Julia; Heuer, Luisa D.; Szavay, Philipp O.; Zundel, Sabine (European Journal of Pediatric Surgery, 2022)
Introduction The highest percentage of female surgeons is found in pediatric surgery but most departments are led by men. The aim of this study is to evaluate gender-related career goals, perceived career opportunities, and reasons for differences.Materials and Methods An online questionnaire was created and distributed to pediatric surgeons in Germany, Switzerland, and Austria between July and September 2020. Participants were asked to state current position, career goals, and perceived career opportunities in comparison to a colleague of the opposite gender. Reasons for gender-related differences were asked for as free-text comments.Results A total of 182 questionnaires were analyzed. The overall gender ratio was balanced but junior positions were predominantly held by women, while there were more men in leading positions. Most women pursued a position as a consultant, while the majority of men aimed for a leading position. Men mostly regard both genders to have the same career opportunities, whereas most women believe the chances of men to be better. From the free-text answers, three following categories for gender-related differences in career chances were derived: (1) absences due to maternity, (2) differing support and bias arising from gender-related stereotypes, and (3) assumed personality traits.Conclusion There are gender-related differences in career opportunities in pediatric surgery. Gender equality is needed not only to overcome injustice but also to maximize team efficiency and collaboration. Career support needs to be gender-independent and (unconscious) bias needs to be recognized and eradicated.
Keywords: gender; pediatric surgery; career opportunities